Spreading the good news : a publicity & promotional campaign for 1VOX the music workshop - Chen, Faith Yireng (2008)
This report provides an insight into the promotional and publicity campaign our group undertook for 1Vox the Music Workshop, a cafe situated at Funan the IT mall.